Heat and mass transfer of an oscillatory flow with Hall current, II - Agrawal H.L.; Ram P.C.; Singh V. (My University, 2025)
An analysis of Hall current on the combined effects of thermal and mass diffusion of an electrically conducting liquid past an infinite vertical porous plate is performed. Analytical expressions for the transient velocity, the transient temperature in the boundary layer and the skin-friction on the plate are derived. The effects of various parameters on the velocity, temperature, shearing stresses and rate of heat transfer are shown by graphs and tables. © 1983 D. Reidel Publishing Co.